Alkaloid from Alstonia yunnanensis diels root against gastrointestinal cancer: Acetoxytabernosine inhibits apoptosis in hepatocellular carcinoma cells - Lai, Qi; Yang, Chun-Ju; zhang, Qi; Zhuang, Min; Ma, Yan-Hua; Lin, Cheng-Yuan; Zeng, Guang-Zhi; Yin, Jun-Lin (Frontiers in Pharmacology, 2023)
Abstract: Liver cancer belongs to Gastrointestinal (GI) malignancies which is a common clinical disease, a thorny public health problem, and one of the major diseases that endanger human health. Molecules from natural products(NPs) or their derivatives play an increasingly important role in various chronic diseases such as GI cancers. The chemical composition of the Alstonia yunnanensis Diels roots was studied using silica column chromatography, gel chromatography, recrystallization, and HPLC, and the compounds were structurally identified by modern spectral analysis using mass spectrometry (MS) and nuclear magnetic resonance (1H-, 13C-, HMQC-, HMBC-, and 1H-1HCOSY-NMR), ultraviolet and visible spectrum(UV), and electronic Circular Dichroism (ECD). Acetoxytabernosine (AC), an indole alkaloid with antitumor activity, was isolated from Alstonia yunnanensis Diels root. The current study aimed to investigate the influence of AC on the cell proliferation of BEL-7402 and SMMC7721 and to elucidate the underlying mechanism. The absolute configuration of AC was calculated by ECD (electronic circular dichroism). The effects of AC on the viability of different tumor cell lines were studied by the SRB method. The death mode of human hepatoma cells caused by AC was studied by TUNEL cell apoptosis detection and AnnexinV-FITC/PI double staining image. The effects of AC on the expression of apoptosis-related proteins (Caspase9, Caspase3, and Parp-1) in SMMC7721 and BEL-7402 cells were detected by western blot. It was found that the absolute configuration of AC is 19(s), 20(s)-Acetoxytabernosine. AC could induce apoptosis of SMMC7721 and BEL-7402, and block the replication of DNA in the G1 phase. Under the treatment of AC, the total protein expression of apoptosis-related proteins (Caspase9, Caspase3, and Parp-1) significantly decreased in SMMC7721 and BEL-7402. The results suggested that AC induced apoptosis through a caspase-dependent intrinsic pathway in SMMC7721 and BEL-7402, and natural product-based drug development is an important direction in antitumor drug discovery and research.